Unhealthy places : the ecology of risk in the urban landscape - Fitzpatrick, Kevin M. (Routledge, 2000)
Unhealthy Places focuses on issues of health in today's cities. By arguing that "place matters" in relation to the population's health, Kevin Fitzpatrick and Mark LaGory make a convincing argument about the general unhealthiness of urban environments and, thus, of the urban dweller. The authors offer a place-oriented approach to health and cover such topics as the ecology of everyday urban life, the sociology of health, needs and risks of the socially disadvantaged, needs and risks of children and the elderly in cities, and strategies for better health services in urban environments